The Reflective Teacher – A Promoter of Change in Education - Șova, Tatiana (Didactica Danubiensis, 2026)
The article analyzes the concept of the reflective teacher as a promoter of change in education, highlighting the role of pedagogical reflection in the context of profound transformations of contemporary educational systems, marked by complexity, uncertainty, and dynamism. The analysis is based on classical concepts of reflection and recent studies on reflective training of teaching staff, arguing that effective teaching practice is not reduced to mechanical application of theories; it rather requires a systematic and critical examination of one’s own professional experience. The reflective teacher is described as a practitioner who constantly mediates between theory and practice, transforming problematic educational situations into opportunities for learning and pedagogical innovation. The article highlights the forms of reflection - knowledge-in-action, reflection-in-action, and reflection-on-action - and the impact of their interaction on pedagogical change and professional development. The author analyses structured models of reflection proposed by noted researchers in the field that provide rigorous methodological frameworks to transform experience into professional competence and integrate the emotional dimension of teaching. Furthermore, the article draws upon results from recent research regarding professional learning communities and collaborative reflective practices, emphasizing the importance of a climate of trust, constructive feedback, and teamwork to achieve sustainable educational change. In conclusion, it is stated that the reflective teacher is a key actor in pedagogical innovation, contributing to the increase of educational quality, development of professional autonomy, and adaptation of the educational process to students’ needs and the demands of contemporary society.